Optimization of the intermediate precooling temperatures for the 2 K hybrid cryocooler based on entropy generation analysis - Bangjian Zhao; Shihang Ding; Lixi Lu; Zhen Yang; Guoliang Tang; Shijie Liu; Chunlai Li; Guangjun Dong; Jianyu Wang (Case Studies in Thermal Engineering)
There is an increasing demand for 2 K hybrid cryocoolers, consisting of a multi-stage Stirling-type pulse tube cryocooler (SPTC) coupled with a Joule-Thomson cooler (JTC), due to their critical applications in deep space exploration and quantum information technology. Precooling temperature and the number of precooling stages, as the key parameters of hybrid cryocoolers, are crucial for attaining 2 K cooling performance. In this paper, an entropy model of the JT cryocooler at 2 K temperature is established for the first time. Based on this model, three-stage precooling temperatures under various operating conditions are optimized, minimizing entropy generation and enhancing the energy utilization efficiency of the JTC cycle in the hybrid cryocooler. Results indicate that there is an optimal value for the first stage precooling temperature (Tpre.1) of 105 K, and the second-stage precooling temperature (Tpre.2) should be minimized. The third stage precooling temperature (Tpre.3) varies with the first two stages and is uniquely determined. Increasing precooling stages from two to three cuts entropy generation by about 15.12 %. These findings offer a key theoretical basis for optimizing hybrid cryocooler design and improving its efficiency and performance.